Measuring Early Childhood Mathematical Cognition: Validating and Equating Two Forms of the Research-Based Early Mathematics Assessment. (December 2021) - Dong, Yixiao; Clements, Douglas H.; Day-Hess, Crystal A.; Sarama, Julie; Dumas, Denis
Psychometric work with young children faces the particular challenge that children's attention spans are relatively short, and therefore, shorter assessments are required while retaining comprehensive coverage. This article reports on three empirical studies that encompass the development and validation of the research-based early mathematics assessment-short form (REMA-SF), an instrument that measures the early mathematical competency of children from 3 to 8 years of age. The developed measure captures both children's mathematical performance and the strategies children use to solve math problems. Results indicated that the REMA-SF can produce valid scores for measuring children's math skills in early childhood, and the validity of the measure can be well-generalized to an external (or independent) sample. Additionally, we also equated the REMA scores between the long and short forms of the assessment: anchor items common across the forms were selected and refined in the equating process.